Cover Image. Issue 2 (31st January 2023) - Unknown
Abstract : To illustrate preparation of an upper extremity for transplantation in a scientifically accurate way, we decided to focus on the technology behind it, with less emphasis on the extremity itself. While the extremity gets amputated during its procurement, exposing this view could be unpleasant to viewers. So, cocooning it in a support chamber seemed like the best way to convey the message without compromising on scientific accuracy.